Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.3758/s13421-010-0050-3
|View full text |Cite
|
Sign up to set email alerts
|

How prior knowledge affects selective attention during category learning: An eyetracking study

Abstract: Research has shown that category learning is affected by (a) attention, which selects which aspects of stimuli are available for further processing, and (b) the existing semantic knowledge that learners bring to the task. However, little is known about how knowledge affects what is attended. Using eyetracking, we found that (a) knowledge indeed changes what features are attended, with knowledge-relevant features being fixated more often than irrelevant ones, (b) this effect was not due to an initial attentiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 51 publications
3
36
0
1
Order By: Relevance
“…Another study on visual category learning found that semantic category knowledge can help to direct attention to relevant stimulus dimensions (Kim and Rehder, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Another study on visual category learning found that semantic category knowledge can help to direct attention to relevant stimulus dimensions (Kim and Rehder, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Closely related to studies of prior knowledge and learning is the study by Kim and Rehder (2011) on selective attention and prior knowledge. According to Kim and Rehder (2011), "little is understood about how knowledge affects attention," (p. 650) but investigating this gap in understanding is important "because any theory of how knowledge influences learning is incomplete without an account of how it alters what category information is attended and thus processed" (p. 650). Since almost nothing is known about the interaction of prior knowledge and attending, the researchers chose eye tracking as a "relatively direct measure of selective attention during knowledge-based category learning" (Kim & Rehder, 2011, p. 650).…”
Section: )mentioning
confidence: 99%
“…Since almost nothing is known about the interaction of prior knowledge and attending, the researchers chose eye tracking as a "relatively direct measure of selective attention during knowledge-based category learning" (Kim & Rehder, 2011, p. 650). Researchers Kim and Rehder (2011) decided on three main questions of inquiry, the first of which was: Does knowledge induce any change to what is attended; i.e., to direct toward one at the expense of another? Kim and Rehder (2011) pointed to research showing connections between "encoding and inferential processes but not selective attention" (p. 650) on knowledge and category learning.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…fear, anger, pleasure, hopes, or desire) and sensory information are not amenable to a complete evaluation. Even the conscious evaluation process itself, respecting desirable and undesirable values of information, can distract the conscious mind from working on each experience (Kim and Rehder 2011). …”
Section: How Human Memory Acquires Information: Conscious and Unconscmentioning
confidence: 99%